Toward a great and enduring profession. - Wing, Michael (Software engineering notes.)
SE is emerging from years of turmoil. Practitioners are beginning to stand up for themselves and their profession. I have seen them do so in Technology Review and heard them on NPR. Practitioners are fighting for their jobs, against outsourcers, like the SEI.